"White Skin": Lyotard's Sketch of a Postcolonial Libidinal Economy. Issue 51 (1st October 2020) - Woodward, Ashley
ABSTRACT: In 1975 Jean-François Lyotard published a short text entitled Pacific Wall. A mash-up of philosophy, fiction, biography, and art criticism, it is highly gnomic if read in isolation. Studied alongside other works from this period, however, it may be understood as sketching a postcolonial libidinal economy. The book's central concept, "white (or blank) skin" avoids any simple identification and instead expresses a series of permutations of desire in relation to race and sex: it is equally the skin of white heterosexual women and of black homosexual men; equally the otherness at the borders of capital's expansion and the supposed identity at the heart of Empire. Lyotard suggests that political issues endemic to the postcolonial situation may be understood in terms of feelings such as lust, jealousy, fear, and the desire for revenge, and that these circulate and mutate along with the flows and transformations of capital.